Prevalence and Trends in Percutaneous Endoscopic Gastrostomy Placement: Results From a 10-Year, Nationwide Analysis - Folwarski, Marcin; Klek, Stanislaw; Brzeziński, Michał; Szlagatys-Sidorkiewicz, Agnieszka; Wyszomirski, Adam; Meyer-Szary, Jarosław; Skonieczna-Żydecka, Karolina (Frontiers in Nutrition, 2022)
Background. Percutaneous endoscopic gastrostomy (PEG) is the most commonly used access for long-term enteral nutrition. Only a few studies report the prevalence and epidemiology of PEG placements. No previous data concentrated on the health care system issues influencing the qualification rates and professional nutritional support for individuals with PEG. Methods. We conducted a retrospective nationwide analysis of PEG placements in Poland from 2010-2020. Central data on ICD-10 coding of adult patients with PEG reported to the insurance company was used for the analysis of general and regional prevalence, age, primary and secondary diseases. Rates of patients with home enteral nutrition (HEN) were calculated with a special focus on cancer patients. A secondary aim was to determine the causes of regional disparities among administrative regions. Results. A total number of 90182 PEGs were placed during the observation period. The number was increasing each year with statistical significance. Malnutrition, dysphagia and cardiorespiratory/metabolic diseases were the most frequently reported as primary disease. A total of 11.98% of all patients were diagnosed with cancer; 49.9% of oncological patients suffered from head and neck cancer (HNC) and 19.9% from esophageal cancer. 6.61% of HNC and 27.46% of esophageal cancer patients from the Polish National Cancer Registry had PEG. The rates of patients in more advanced age (65-74 and over 85) were growing and decreased in younger groups (18-24, 45-54, 55-64). Overall, 17.6% of all (11.86% of cancer) patients with PEG were on reimbursed HEN. A high number of patients in nursing care facilities, lower education of citizens and lower number of hospital beds were associated with more PEG insertions in the administrative regions. Conclusions. The number of PEG placements has been increasing, particularly in the elderly. Systemic solutions must be found to address the problems of regional disparities in PEG’s prevalence as well as the lack of inclusion criteria for nutritional support.